IMPLEMENTING SCIENTIFIC METHOD TO STRENGTHEN THE STUDENT'S SCIENTIFIC ATTITUDE: A STUDY ON BIOLOGY SUBJECT - Chheun, Seyha; Kong, Sam Ol (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
The scientific method was actually defined in many different ways up to the contextual of learning. This study is to implementing scientific method to strengthen the scientific attitude: A case study of Class 8 students in the subject of Biology. The main objective of this research is on how the implementation of Scientific Method affects scientific attitude of grade 8 students in Biology. The samples of this study involved with18 students for observation and 3 students for interviewing. The students were chosen from class8 for data collection. The data analyzing in this research was used Thematic Analysis method with the variation of observation. Based on the observation, the students were not familiar with the scientific method yet at the first time of class compared with the last observation, students processed activities at higher level. All of the criteria of scientific attitudes were contributed. Moreover, the result from interview is supported to the improvement of students’ scientific attitudes by implementing scientific method. Therefore, it can be concluded that, the implementation of scientific method imposed scientific attitudes in the classroom. The findings identified that scientific method strengthen students' scientific attitude toward learning such as: curiosity, honesty and objectivity, critical resonating, open minded and cooperation, and responsibility. The further research should apply scientific method for a longer period to make students to be familiar with the method. Moreover, the researcher should spend more time observing or interviewing teachers to get the result more accurately.